Relationships’ Accuracy with reaction time, balance, some of attacks and defense skills from junior fencing foils players - A. Mohammad, Bassam; H. Mahdi, Abdolhadi (Journal of Physical Education, 2012)
Fencing sport dependent in attacks’ and defense moves and keeps the distance between players and controlling the attacks fake from opponents in faster to gain the Accuracy to have the match. Must to gain all the above must joining between all the special physical abilities to perfect basic skills from attacks and defense.The aim from the research to know relationships’ Accuracy with reaction time, balance, some of attacks and defense skills from junior fencing foils players. Hypothecs that we found statically relationships’ between the Accuracy with reaction time, balance, some of attacks and defense skills from junior fencing foils players. The followings are the main conclusions that real statically relationships’ between the most of like accuracy with lunge and some of attacks and defense skills, reaction time, balance, from junior fencing foils players. The main recommendations are the following: - Implementing the true performance of attacks and defense skills and establish the new program for repeat frequency in deferent shapes to gain improvement the learning and made the conclusions in famous and last doing similar studies to enhance other kind of players and gender..